American journal of physical anthropology : official publication of the American Association of Physical Anthropologists - American Association of Physical Anthropologists; Johnston, Francis E. (New York : Alan R. Liss, Inc., 1982)
"The American Journal of Physical Anthropology is designed for the prompt publication of original and significant articles on human evolution and variation, including primate morphology, physiology, genetics, adaptation, growth, development, and behavior present and past."
Abstracts of papers to be presented in the meeting
Includes index.
In English.
Keywords: Physical anthropology -- Periodicals. Societies. Serials; Antiquities, Prehistoric; Prehistoric peoples